Preparation and Characterization of Doripenem-Loaded Microparticles for Pulmonary Delivery - DURMUŞOĞLU, LÜTFİYE (MARY ANN LIEBERT, INC, 2018)
Background: Pneumonia is a bacterial lower respiratory tract infection that has a high morbidity rate. The gram-negative pathogen Pseudomonas aeruginosa is a significant cause of nosocomial infections and ventilator-associated pneumonias and is mainly treated by carbapenems. Doripenem is a carbapenem drug, which has a broad-spectrum antibacterial activity. The aim of this study was to develop doripenem-loaded chitosan microparticles for pulmonary administration to provide more efficient treatment for pneumonia. Methods: Ionotropic gelation and the spray-drying method were used to obtain doripenem-loaded chitosan microparticles with different lactose, trehalose, and L-leucine concentrations. Physicochemical characteristics, in vitro drug release properties, and aerodynamics properties were investigated and in vitro antimicrobial susceptibility tests of the formulations were performed. Assessment of aerodynamic properties of the powders, including Mass Median Aerodynamic Diameter, size distribution, and fine particle fraction (FPF), were performed using a Next Generation Impactor. Cytotoxicity of the fabricated microparticles was assessed using the Calu-3 cell airway epithelial cell line. Results: Optimum microparticles were produced using a combination of ionotropic gelation and spray-drying methods. Spray-dried microparticle production yield was relatively high (74.03%3.88% to 98.23%+/- 1.70%). Lactose, trehalose, and L-leucine were added to the formulation to prevent aggregation produced by the ionotropic gelation spray-drying method. Each formulation's encapsulation efficiency was above 78.98%+/- 2.37%. The doripenem-loaded microparticle mean diameter ranged from 3.8 +/- 0.110 to 6.9 +/- 0.090m. Microparticles with 20% (w/w) L-leucine had the highest FPF ratio indicating the best aerosolization properties of the formulations. The efficacy of the formulations as an antibacterial agent was increased by forming doripenem-loaded microparticles compared to blank microparticles. P. aeruginosa showed the same susceptibility to all doripenem-loaded microparticle formulations. Cell viability of microparticles was between 70%+/- 0.08% and 90%+/- 0.04% at 0.5 and 10mg/mL concentration, respectively. Conclusions: Doripenem-loaded microparticles, produced using a combination of ionotropic gelation and spray-drying methods, are suitable for pulmonary drug delivery based on their particles size, zeta potential, cytotoxicity and high production yield. To our knowledge, this is the first study that microparticles containing doripenem were produced and characterized.
Keywords: doripenem; microparticles; pneumonia; pulmonary drug delivery; GRAM-NEGATIVE BACILLI; IN-VITRO ACTIVITY; AEROSOLISATION PROPERTIES; PSEUDOMONAS-AERUGINOSA; CHITOSAN MICROSPHERES; FORMULATION; S-4661; NANOPARTICLES; ENCAPSULATION; OPTIMIZATION